ASUHAN KEPERAWATAN PADA TN. T DENGAN DEMAM TYPHOID DI RUANG RAWAT INAP CENDANA II RS BHAYANGKARA TK. I R. SAID SUKANTO - Berlian Rahmah Pertiwi (2022)
Introduction Typhoid fecer is a bacterial infectious disease of Salmonella Typhi that has been contaminated with feces or urine from typhoid sufferes is used to attack the gastrointestinal tract. The research method used in this research is a descriptive method by taking a case study approach. The Results showed that the main nursing problems were hyperthermia, diarrhea, acute pain, and nausea. The main nursing action applied is to apply a warm compress. The Conclusion obtained in the discussion with hyperthermia wa find that there was a gradual decrease in temperature from 38oC to 36,5oC. Suggestion are expected to personal hygiene and be able to perform first aid in dealing with typhoid fever.